Pembiasaan Shalat Tahajud Berjamaah Dalam Meningkatkan Kedisiplinan Santri Putri Mt Al-Iffah Badean Bondowoso Tahun 2023 - Anshari, Zainal; Triana, Linda (Akademika, 2023)
The habit of praying the midnight prayer in congregation is an activity that is carried out after the evening prayer until dawn, but the best time or the most important time to do the midnight prayer is the last third of the night. With the habit of praying midnight in congregation, this can improve the discipline of the santri. Based on this background, the focus of the research is: (1) How is the implementation of the habituation of the midnight prayer in congregation in improving the discipline of female students at MT Al-Iffah Badean Bondowoso in 2023? (2) What are the supporting and inhibiting factors in the habit of praying midnight prayers in congregation in improving the discipline of female students at MT Al-Iffah Badean Bondowoso in 2023? This study aims to describe the implementation of the Habituation of Congregational Prayers in Improving the Discipline of female students at MT Al-Iffah Badean Bondowoso in 2023. And to find out what are the supporting and inhibiting factors of the habituation of congregational prayers in improving the discipline of female students at MT Al-Iffah Badean Bondowoso in 2023. The research approach used is a qualitative approach to the type of case study research. Sources of data in this study were school principals, program administrators, tutors and students. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is Miles, Huberman and Saldana which consists of condensing data, presenting data and drawing conclusions. The results of the study show that 1) Implementation of the habituation of the midnight prayer at MT Al-Iffah is required to be in congregation, not only the students but the administrators are also required to pray the midnight prayer in congregation. For the implementation of the midnight prayer starting at 03.15, before the implementation of the 15 minutes is used for preparation, namely by reciting the surah al-waqiah and reading the asmaul husna while waiting for all students to finish taking ablution water, for those who do not perform the midnight prayer in congregation will get a punishment from the worship administrator. 2) The supporting factors are the discipline of the students, the awareness of the students, and the presence of administrators while the inhibiting factors are the lack of intention, irregular sleep, and drowsiness.